(untitled) (Global Journal of Management and Business Research, 2016)
Female Entrepreneurship is considered an important tool for female empowerment and emancipation. The main objective of this study is to investigate self-employment perception of female undergraduates students (Comparison Ethiopian Public and Private Universities). Entrepreneurship has become a crucial area to study and understand -especially with respect to, perception toward entrepreneur, motivations, constraints and consequences. Female undergraduates students are chosen for the current study is because they are at a period in their career development where they are considering different career routes and are therefore, a potential source of future female entrepreneurs. The finding of the study identified that there were different factor that affects female undergraduates’ perception self-employment.